Effects of Al distribution in the Cu-exchanged AEI zeolites on the reaction performance of continuous direct conversion of methane to methanol - Xiao, Peipei; Wang, Yong; Lu, Yao; De Baerdemaeker, Trees; Parvulescu, Andrei-Nicolae; Müller, Ulrich; De Vos, Dirk; Meng, Xiangju; Xiao, Feng-Shou; Zhang, Weiping; Marler, Bernd; Kolb, Ute; et al. (Applied catalysis. B, Environmental, 2023)
The effects of the organic structure-directing agent (OSDA) with or without Na cations for the synthesis of AEI zeolite on the location and content of the Al atoms in the framework as well as the Cu speciation and acidic features of the exchanged Cu/AEI zeolite catalysts and their catalytic properties in the continuous direct conversion of methane to methanol (cDMTM) were investigated. The AEI zeolite synthesized with Na cations led to more Al and a higher percentage of Al pairs than the one prepared without Na cations. Consequently, the Cu/AEI zeolite catalysts synthesized with Na cations exhibited lower apparent activation energy of methane conversion, higher methanol formation rate, and less stable ability in the cDMTM reaction due to the more active dicopper species and higher acid amount than those prepared without Na cations. Adjustment of the close Al content in the framework of the two AEI zeolites by calcination, the Cu/AEI zeolite synthesized with Na cations evidenced a higher methanol selectivity and more stable reaction performance because of the different relationship between Cu species and acid sites, such as the distance, caused by the Al distribution. The methanol formation rate of 27.3 µmol·g−1·min−1 with about 50% selectivity and stable performance in the cDMTM reaction at 350 °C were obtained. Moreover, the stability of both 5Cu/AEI zeolite catalysts could be upgraded by further calcination to diminish the acid amount, the high methanol formation rate of the 5Cu/AEI zeolite synthesized with Na cations was maintained and the reaction stability was newly attained. The 5Cu/AEI zeolite synthesized without Na cations, merely the stable performance was reached, while the methanol formation rate and selectivity seriously declined. This work contributed to the development of AEI zeolite with different Al distributions and its significant impacts on the Cu speciation and acidic properties, thus providing a valuable strategy to obtain a robust Cu/AEI zeolite catalytic system for efficient and stable methanol production from methane. [Display omitted] •AEI zeolites with different distributions and contents of Al were synthesized with or without Na.•Cu/AEI(Na) zeolite obtained more dicopper species and acid amount.•Cu/AEI(Na) achieved higher methanol formation rate and selectivity.•The close Al content in the framework of AEI(Na) and AEI(Na free) was attained by calcination at different temperatures.•The similar maximum methanol formation rate but different stability of Cu/AEI(Na) and Cu/AEI(Na free) were obtained after regulation the close Al content in the framework.